Motivations and Attitudes Toward Voluntary Oocyte Donations. Experience of the Reproductive Medicine Unit of Monteblanco Clinic [Motivaciones y Actitudes Hacia la Donación Voluntaria de Ovocitos. Experiencia de la Unidad de Medicina Reproductiva de la Clínica Monteblanco] - Schwarze-Meza, J (Sociedad Chilena de Obstetricia y Ginecologia, 2012)
Aims: To identify the motivating factors of candidates to donate oocytes, and the significance they assign to oocyte donation. Methods: We evaluated 18 volunteers trough a semi-structured interview. Topics discussed included: past experiences, fantasies and expectations towards the process of oocyte donation. Results: The ages fluctuated between 19 and 29 years; 13 were single and 6 had one or more children. More than a half were studying and working at the moment of the interview. None had familiar or personal psychiatric disorders. The economical compensation was the most important reason for the intention to donate, though the empathy with infertile couples was a significant motivator too. Potential donors perceived anonymity as protective for both donor and receptor. They perceived motherhood as rising the child rather than having a genetic link. Conclusions: We found that potential donors perceive motherhood as linked to rising a child, rather than having a genetic link. Therefore, they assimilate oocyte donation to the donation of any other organ. However, they prefer to have no contact with the oocyte receptor. As expected, the main motivator is the economical compensation, however they have strong feelings of empathy towards infertile couples.